THEOLOGICAL POLITICS: AN ANALYSIS OF AMBITION FOR AUTHORITY AND POWER IN THE LIGHT OF PROPHETIC HADITH - Kusnandar, Engkus; Kirom, Syahrul; Yani, Ahmad (Jurnal Studi Hadis Nusantara, 2024)
Humans as political beings have the character to rule and dominate. And Islam as a comprehensive religion has regulated human life to remain within the corridor outlined by religion. Therefore, the hadith of the Prophet SAW has regulated and explained the prohibition of asking for positions and power. The purpose of this study is to find out what the Prophet's views and the scholars' views are regarding this prohibition. The approach chosen in this study is descriptive qualitative. The results of the study are that the Prophet's prohibition is local and temporal in nature. It is not absolute or universal. The Prophet's prohibition in his hadith is seen in the context of the person asking for a position not having skills, responsibility and not being trustworthy. This study shows that being ambitious or asking for a position is permissible, even highly recommended, if the following conditions exist: (1). The competitors or presidential/regent candidates are oppressors. (2). The candidate leaders or officials are infidels. (3). The competitors or candidates for officials do not have the skills or expertise. (4). The competitors or candidates for officials are immoral and greedy for power. (5). Asking for a position is permissible after we have first been offered a position by a ruler.